Patent activity in the field of decarbonization technologies - A. R. Sadriev; M. S. Kuzmin (Модернизация, инновация, развитие, 2023)
Purpose: the aim of the research is to explore the global trends in the development of the inventive space in the field of decarbonization and to identify the degree of their compliance with the patterns of patent activity in the Russian economy.Methods: patent data for the period 2010–2022, aggregated by the search engines of Rospatent, the World Intellectual Property Organization, Google Patents, Espacenet and Questel Orbit, were used to conduct the research. The analysis of global inventive activity in the field of decarbonization was provided for Class Y02, subclass Y04S and group B09 of the Cooperative Patent Classification (CPC). The analysis of patenting pattern in the Russian economy was performed in accordance with the codes of the IPC Green Inventory. The relative technological advantages of Russia in the development of technologies to achieve carbon neutrality are analyzed on the basis of data from the RTA (Revealed Technology Advantage) index.Results: it was established that the high dynamics of global inventive activity in the field of decarbonization has not yet led to a multiple gap between patents and patent families, which indicates that a large volume of technological developments in the field of carbon neutrality are at relatively early stages of market maturity. It was determined that the leading positions of developers of relevant technological solutions are shifting from Japanese to Chinese and South Korean companies that are actively developing such advanced technological directions as energy storage and its production using alternative sources. Russian copyright holders demonstrate a relatively higher specialization in developments for nuclear power and railway transport systems, unlike foreign representatives. The decarbonization areas represented by domestic developments in the field of alternative energy production are characterized by significantly lower values of RTA index.Conclusions and Relevance: the space of inventive activity in the field of decarbonisation technologies forms the ability to identify and analyse a network of both explicit and non-obvious interrelations of these technologies with developments from other technological fields. This approach determines the possibility of purposeful design interdisciplinary cooperation chains between developers of indirectly correlated technological developments and manufacturers of the end products.